Trends in Microalgae Incorporation Into Innovative Food Products With Potential Health Benefits - Caporgno, Martín P.; Mathys, Alexander (Frontiers in Nutrition, 2018)
Microalgae have demonstrated potential to meet the population’s need for a more sustainable food supply, specifically with respect to protein demand. These promising protein sources present several advantages over other currently used raw materials from an environmental point of view. Additionally, one of the main characteristics of microalgae is the production of bioactive compounds with potential benefits for human health. Microalgae exploitation as a source of protein (bulk protein) and other valuable products within the food industry still presents some drawbacks, mainly because of the underdeveloped technologies and processes currently available for microalgae processing. The technology readiness level (TRL) could help change the current situation if applied to microalgae cultivation and processing. High maturity in microalgae cultivation and processing technologies also requires improvement of the economy of scale and investment of resources in new facilities and research. Antioxidative, antihypertensive, immunomodulatory, anticancerogenic, hepato-protective, and anticoagulant activities have been attributed to some microalgae-derived compounds such as peptides. Nevertheless, research on this topic is scarce and the evidence on potential health benefits is not strong. In the last years, the possibility of using microalgae-derived compounds for innovative functional food products has become of great interest, but the literature available mainly focuses more on the addition of the whole cells or some compound already available on the market. This review describes the status of utilising microalgae as an ingredient in innovative food products with potential health benefits.